2017
DOI: 10.1039/c7ay00690j
|View full text |Cite
|
Sign up to set email alerts
|

Surface acoustic wave devices for chemical sensing and microfluidics: a review and perspective

Abstract: Surface acoustic waves (SAWs), are electro-mechanical waves that form on the surface of piezoelectric crystals. Because they are easy to construct and operate, SAW devices have proven to be versatile and powerful platforms for either direct chemical sensing or for upstream microfluidic processing and sample preparation. This review summarizes recent advances in the development of SAW devices for chemical sensing and analysis. The use of SAW techniques for chemical detection in both gaseous and liquid media is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
111
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(115 citation statements)
references
References 189 publications
(213 reference statements)
1
111
0
Order By: Relevance
“…The sensing mechanism of surface acoustic wave (SAW)-type sensors is as follows: the captured molecules on the surface of the SAW device functionalized with synthetic receptors affect the frequency of the SAW, suggesting that the shifts in the frequency reflect the sensing information of the receptors sensitively [90]. Although the detection of various gas molecules such as volatile organic compounds (VOCs) has been demonstrated using SAW-based sensors modified with molecular assemblies [55,91,92], the sensing of aqueous molecules utilizing the combination of SAW devices with synthetic receptors is still rare due to the low signal-to-noise ratio of SAW sensors in aqueous media [90]. Recently, Zhang et al reported an amplification strategy for the output signal in the SAW-based sensor in the detection of biomolecules (exosomes) by using biomaterial-functionalized nanoparticles [93].…”
Section: Nanosensor Platforms Based On Other Physical Parametersmentioning
confidence: 99%
“…The sensing mechanism of surface acoustic wave (SAW)-type sensors is as follows: the captured molecules on the surface of the SAW device functionalized with synthetic receptors affect the frequency of the SAW, suggesting that the shifts in the frequency reflect the sensing information of the receptors sensitively [90]. Although the detection of various gas molecules such as volatile organic compounds (VOCs) has been demonstrated using SAW-based sensors modified with molecular assemblies [55,91,92], the sensing of aqueous molecules utilizing the combination of SAW devices with synthetic receptors is still rare due to the low signal-to-noise ratio of SAW sensors in aqueous media [90]. Recently, Zhang et al reported an amplification strategy for the output signal in the SAW-based sensor in the detection of biomolecules (exosomes) by using biomaterial-functionalized nanoparticles [93].…”
Section: Nanosensor Platforms Based On Other Physical Parametersmentioning
confidence: 99%
“…However, studies implementing SAW for detection of DNA with high optimized frequencies are limited. Nonetheless, SAW-based devices may have the opportunity to become a major player with the prospective commercialization of medical devices that require highly sensitive, selective, and cost-effective analysis [36].…”
Section: Mass-basedmentioning
confidence: 99%
“…In addition, the delay between the transmitted and received signal can restrict the real‐time sensing. Therefore, properties of SAW sensors are not appropriate for frequency range of speech recognition …”
Section: Introductionmentioning
confidence: 99%